Implementation of Islamic Values in Daily Life for Character and Behavior Formation - Fakhrun Nisa; Putri Khotimah; Muhammad Delpie Firdaus; Rizki Riyan Khoirulanshori; Salsabila Salsabila; Afifah Ismahani Nur Amalina (CV. Bimbingan Belajar Assyfa, 2024)
This research analyzes the implementation of Islamic values in shaping the disciplined character and responsible behavior of 3rd-grade students at Madrasah Salafiyah Ula Nashrus Sunnah, Madiun City. The moral crisis among the younger generation demonstrates the urgency of strong character education from an early age, with Islamic values serving as its foundation. This study employs a qualitative approach with a case study method, involving observation, interviews, and documentation of students, teachers, and the principal. The results show that the implementation of Islamic values through the habituation of morning dhikr, Dhuha prayer, congregational Dzuhur prayer, the jimpitan (alms) program, and greeting/salam practices significantly improves students' discipline and responsibility. Students become more obedient to rules, punctual, and demonstrate initiative in tasks and social care. Despite challenges such as consistency outside school and diverse family backgrounds, the findings confirm that Islam-based character education is effective in shaping individuals with high integrity and morality. Strong synergy between school and family, as well as teacher creativity, is needed for the sustainability of this program.